Observing minibeasts - Harlow, Rosie; Morgan, Gareth; Chen, Kuo Kang; Oxford Illustrators Ltd. (New York, N.Y. : Warwick Press, 1991)
Simple experiments introduce the characteristics and behavior of worms and other small animals.
"First published in 1991 by Kingfisher Books"--Colophon.
Includes index.
6.5
6.5
3-6.
3-6
Keywords: Invertebrates -- Juvenile literature; Invertebrates -- Experiments -- Juvenile literature; Experiments; Invertebrates -- Experiments; Invertebrates -- Experiments